Association between cultural capital and health literacy during the COVID-19 pandemic among community residents in China: the mediating effect of social capital - Luo, Yi; Zhao, Hang; Chen, Huayong; Xiao, Mimi (Frontiers in Public Health, 2023)
Background: Health literacy is crucial for managing pandemics such as COVID-19 and maintaining the health of the population; our goal was to investigate the impact of cultural capital on health literacy during the COVID-19 pandemic among community residents and to further examine the mediating role of social capital in the relationship between cultural capital and health literacy.A cross-sectional study was conducted among 1600 community residents selected in Chongqing, China using a stratified random sampling method. Data were gathered through a questionnaire survey, including sociodemographic characteristics, cultural capital, social capital, and health literacy. Chi-square analysis, one-way ANOVA, t-test, and hierarchical linear regression were used to analyze the level of health literacy among community residents and the related elements; the structural equation model(SEM) was used to explore the influential mechanisms of health literacy and explore whether social capital acted as a mediator in the relationship between cultural capital and health literacy.Results: Cultural capital, community participation, community trust, reciprocity, and cognitive social capital had a significant positive effect on health literacy. In addition, the results of SEM indicated that cultural capital not only directly influences health literacy (β =0.383, 95% CI=0.265-0.648), but also indirectly influences health literacy through three types of social capital (β =0.175, β =0.191, β =0.028,; its mediating effect accounting for 50.7% of the overall effect.Our results highlight the empirical link between cultural capital and health literacy, and suggest that social capital mediates this connection. These findings suggest that governments and communities should focus on the construction of community cultural capital and provide residents with better social capital to improve their health literacy to prepare for future pandemics.